PERAN CREDIT CARD USAGE DALAM ONLINE IMPULSE BUYING DI KOTA DENPASAR - Putu Bagus Wichitakani Wahyu Cakraningrat (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
This study aims to determine the effect of materialism, endorsement and brand image on online impulse buying in Denpasar City and also to see whether credit card usage can moderate the relationship between them on online impulse buying. The population of this research are consumers who have made unplanned purchase online domiciled in Denpasar City, with a sample of 135 respondents. Sampling using a purposive sampling technique. Collecting data using an online questionnaire with a Likert scale measurement tool. The type of data used in this study is quantitative data. The data analysis method used in this study uses validity test, reliability test, classic assumption test, and Moderated Regression Analysis (MRA) using the SPSS version 24.0 application for Windows. The results of this study stated that the variable materialism and endorsement had a positive and partially significant effect on online impulse buying, whereas the variable brand image had a negative and partially significant effect on online impulse buying in Denpasar City. Also, the moderating variable credit card usage is able to strengthen the effect of brand image on online impulse buying in Denpasar City. This study is expected to provide an understanding of marketers which can later be used to design efforts that are possible to be applied by service or product providers to increase online impulse buying of consumers and their target consumers.